Anti-bacterial efficacy of bio-fabricated silver nanoparticles of aerial part of Moringa oleifera lam: Rapid green synthesis, In-Vitro and In-Silico screening. (January 2022) - Neupane, Netra Prasad; Kushwaha, Amit Kumar; Karn, Abhishek Kumar; Khalilullah, Habibullah; Uzzaman Khan, Mohd Masih; Kaushik, Ajeet; Verma, Amita
Abstract: Purpose: Silver nanoparticles have been extensively used in pharmaceutical sciences as therapeutic agents, including in drug delivery but their toxicity towards healthy tissue is not explored from trials. Being herb, Moringa oleifera lam (MO) is cheap, eco-friendly, non-toxic as compared to synthetic nanoparticles. The antibacterial efficacy of silver nanoparticles of aerial parts of M. oleifera lam and bactericidal mechanisms have not been explored so far. Methods: In this study, rapid biosynthesis of M. oleifera lam embedded silver nanoparticles (MONPs) was acquired using M. oleifera lam aerial parts, and characterized by using UV, Fourier transform infrared spectroscopy (FTIR), Scanning electron microscopy (SEM), Transmission electron microscopy (TEM), and X-ray diffractometer (XRD) studies. Well diffusion method was used to assess the zone of inhibition and minimum inhibitory concentration of the MONPs on Escherichia Coli, Pseudomonas aeruginosa, Staphylococcus aureus, Salmonella typhi . The probable mechanism of action was accessed through molecular docking and simulation. Results: The size of AgNPs was spherical with less than 50 nm size and showed a crystalline peak at XRD. MONPs at 250 μg/ml inhibit the growth of all the gram-positive and gram-negative bacteria with significant antibacterial affinity. The minimum inhibitory concentration of MONPs was lower in gram-positive bacteria than gram-negative bacteria. The molecular docking studies of phytoconstituents present in MO showed luteolin (−9.2 kcal/mol) and rutin (−10.1 kcal/mol) have higher binding energy with DNA gyrase & tyrosyl tRNA synthetase inhibitors respectively. Molecular simulations study confirmed that both ligands have a good stability profile by forming different bonds with active site amino acids. Conclusion: Bio-fabricated silver nanoparticles exhibited noteworthy gainful impacts against selected bacterial strains and could serve as a lead for future antibacterial drug discovery. Graphical abstract: Image 1 Highlights: Cost effective rapid green synthesis of Moringa olifera (MO) embedded silver nanoparticles. Antibacterial screening of MO embedded silver nanoparticles showed significant activity against bacteria. Screening of polyphenolic compounds from MO and docking against bacterial DNA gyrase and tyrosyl tRNA synthetase. Simulation was performed using rutin and luteolin, these ligands showed highest binding energy with 1kzn and 1jij. Pharmacokinetics and ADME studies of selected polyphenolic compounds from MO.